2014
DOI: 10.1186/1472-6874-14-44
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer knowledge and screening behaviors among female university graduates of year 2012 attending national graduate orientation program, Bhutan

Abstract: BackgroundCervical cancer is the leading female cancer in Bhutan. This study describes the level of cervical cancer knowledge and screening behaviors among female university graduates attending the National Graduate Orientation Program (NGOP), 2012.MethodsA cross-sectional study of female graduates attending NGOP was conducted using self-administered anonymous questionnaire developed through literature reviews and expert discussions to elicit information on demographic characteristics, knowledge, screening beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 18 publications
(20 reference statements)
5
47
2
1
Order By: Relevance
“…The study found, among a large sample of female university students across 25 low and middle and emerging economy countries, an overall low participation rate in cervical cancer screening, which is comparable to previous studies in low and middle income countries (Ayinde et al, 2004;Akujobi et al, 2008;Oladepo et al, 2008;2009;Abotchie and Shokar, 2009 Dhendup and Tshering, 2014). In particular because of the high burden cervical cancer in low and middle income countries, more should be done to promote cervical cancer screening in this population.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…The study found, among a large sample of female university students across 25 low and middle and emerging economy countries, an overall low participation rate in cervical cancer screening, which is comparable to previous studies in low and middle income countries (Ayinde et al, 2004;Akujobi et al, 2008;Oladepo et al, 2008;2009;Abotchie and Shokar, 2009 Dhendup and Tshering, 2014). In particular because of the high burden cervical cancer in low and middle income countries, more should be done to promote cervical cancer screening in this population.…”
Section: Discussionsupporting
confidence: 48%
“…This is especially important in those countries participating in this study with a very low participation rate (0-7.1%) among 21-26 year-old students from Southeast Asian countries, India, Pakistan, China, Tunesia, Turkey, Cameroon, Ivory Coast, Madagascar, and Mauritius. Country variations in the prevalence of cervical cancer screening may be due to various country specific factors, including cervical cancer screening policy, publicity on cervical cancer, systematic and active promotion of screening, accessibility of cancer screening services, and social-and cultural factors specific to the Asian population (Lu et al, 2012;Dhendup and Tshering, 2014). Further, the study found that women who rated cervical cancer screening as more important carried it out more often.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…75 members are daily wages and 45 members are workers. (table 6) Out of these members, 410 members were married and 595 members were unmarried [17].…”
Section: Discussionmentioning
confidence: 99%